A collaborative digital oral history collection: Building a digital collection of student scholarship documenting Latino Americans in southeast North Carolina. Issue 1 (April 2017) - Thompson, Beth J; Baugnon, Rebecca A
A collaborative oral history project was recently completed at the University of North Carolina Wilmington (UNCW) by students enrolled in a Spanish seminar course and library faculty and staff members at the University. The course, 'Hispanics in N.C.: Service Learning and Research, ' was created and offered as one component of a public programming grant awarded to UNCW by the National Endowment for the Humanities and the American Library Association through these institutions' initiative called 'Latino Americans: 500 Years of History.' The course provided students with an opportunity to interview individuals in the southeastern North Carolina Latino community about their experiences in the United States. Students captured an audio recording of the interview which they later transcribed and provided a photograph of the interviewee. Library faculty and staff members were tasked with creating a digital collection to highlight the oral histories. Working within a limited time frame and with no funding for the project, the planning and implementation for the digital collection was completed by librarians in the library's Information Technology and Systems, Special Collections, and Technical Services departments. Utilizing technology, systems, and skill sets that were already in place at Randall Library, a final product titled, 'Somos NC: Voices from North Carolina's Latino Community, ' was created. This article seeks to provide a practical discussion of the oral history project, outlining the Library's processes and project workflows as well as assessment and reflections. Synthesizing knowledge gained through the experience, the intent is to provide an example of how, through collaboration and innovation, small to midsized libraries can accomplish similar projects.